Genetic clinical characterization of patients with hereditary ataxias in the state of Portuguesa-Venezuela - Castro-Montesino, Daelys (2021)
Introduction: hereditary ataxias are neurodegenerative diseases that cause functional deterioration. As a consequence of their progressive nature, they lead to disability in affected individuals with severe psychological damage in their families. Objective: to characterize clinically and genetically the patients with hereditary ataxias in the Portuguese-Venezuela state in the period 2013-2015. Methods: an observational, descriptive cross-sectional study was carried out in patients with a diagnosis of hereditary ataxia. The universe consisted of 33 patients diagnosed in the study period, we worked with all of them. The individual and family health histories were reviewed. The data obtained were processed using the SPSS statistical program. Results: there was a predominance of the age group 25-29 years (18.18%) and the male sex (51.5%); as well as adult autosomal dominant spinocerebellar ataxias (SCA1 and SCA2) (82%). Stage 3 disease patients were the most prevalent (40%). The autosomal dominant type of inheritance predominated (69%) and the paternal inheritance path (63%). Conclusions: community genetics and genetic counseling contributed with therapeutic alternatives to improve the quality of life. In addition, the populations at risk were identified to outline preventive actions and reduce the recurrence of hereditary conditions.